Adaptation of circular design strategies based on historical trends and demolition patterns. Issue 1 (1st September 2022) - Andersen, R; Jensen, L B; Ryberg, M W
Abstract: With new knowledge on current trends in construction and demolition, circular design strategies can be adapted to recent developments in construction, thereby providing knowledge about the potential for reducing global warming, resource consumption, and the amount of construction waste. By examining data from public registers on historical demolitions and building statistics, it is possible to examine the patterns in demolished buildings to uncover which building factors may influence whether buildings are demolished or renovated. In the following, data from demolitions in Denmark will be linked to data for newly built and existing buildings. The results show that factors initiating demolition are distributed differently between high- and low-population areas. Furthermore, the increase in new forms of construction means that circular design strategies such as reuse, recycling, and adaptive reuse can only cover a small proportion of the need for new construction.